2022
DOI: 10.1037/hea0001162
|View full text |Cite
|
Sign up to set email alerts
|

Prospective self- and informant-personality associations with inflammation, health behaviors, and health indicators.

Abstract: Objective: Personality influences many aspects of the health process. It is unclear to what extent selfand informant-reports of the Big Five offer incremental validity for the prediction of inflammatory biomarkers and whether inflammation provides a unique pathway between personality and indicators of physical health, independent of health behaviors. Method: Using data from older adults (N = 1,630) enrolled in the St. Louis Personality and Aging Network study, we tested whether self-and informant-reported Big … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…Thus, our study should be considered a first step in examining this and future work is needed to confirm and expand upon the results. Second, different reporting methods were used (parent, self) which have been differently associated with life outcomes 42 , 60 . Third, an alternative explanation for the findings is content and/or structural differences between the two sets of individual differences 2 , 61 .…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Thus, our study should be considered a first step in examining this and future work is needed to confirm and expand upon the results. Second, different reporting methods were used (parent, self) which have been differently associated with life outcomes 42 , 60 . Third, an alternative explanation for the findings is content and/or structural differences between the two sets of individual differences 2 , 61 .…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Agreeableness predicts volunteerism (Penner et al, 1995), religiosity (MacDonald, 2000), disease processes (Miller et al, 1996), and relationship satisfaction (Jensen-Campbell et al, 2002;Robins et al, 2002). Conscientiousness, one of the traits most strongly related to various outcomes, predicts occupational performance and success (Anderson et al, 2001;Barrick et al, 2001), longevity (Jackson et al, 2015), engagement in health and risk behaviors (Bogg & Roberts, 2004;Friedman et al, 2014;Wright et al, 2022), and relationship quality (Solomon & Jackson, 2014). Neuroticism likewise has many strong associations: higher levels predict lower well-being (Smith & Spiro, 2002), psychopathology (Trull & Sher, 1994;Wright & Jackson, 2022b), interpersonal problems (Karney & Bradbury, 1997), and poorer relationship quality (Donnellan et al, 2005).…”
Section: Why Personality Change Should Be Associated With Life Outcomesmentioning
confidence: 99%
“…This is expected if the mechanisms relating trait changes with outcomes reflect the same processes relating trait levels with life outcomes. For example, high levels of conscientiousness are associated with health via health behaviors (Hampson et al, 2007;Lodi-Smith et al, 2010;Wright et al, 2022) and physiological mechanisms (O'Súilleabháin et al, 2021;Wright et al, 2022). Increases in conscientiousness should thus lead to changes in these intermediary processes, such as an increase in health behaviors (Takahashi et al, 2013), thereby leading to greater health-promoting practices.…”
Section: Effects Of Changes In Personality Traits Compared To Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, conscientiousness was positively related to their child's self-reported health status. Conscientiousness is the Big Five trait most routinely linked to health outcomes (Brummett et al, 2006;Hill et al, 2011;Jackson et al, 2015;Jokela et al, 2018;Wright et al, 2022) and is one of the main traits found to have compensatory effects on health in child-mother dyads (van Aken et al, 2007) and other interpersonal dyads such as romantic partners . Thus, the association of parent's conscientiousness with their child's health status, even when controlling for their child's level of conscientiousness, further underscores the utility of having conscientious people in one's social sphere.…”
Section: Parent Personality Is Important For Child Outcomesmentioning
confidence: 99%